CESifo World Economic Survey May 2010 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2010)
World Economic Climate: World Economic Climate improves further - Economic Expectations: Economic expectations slightly downgraded but remain positive - Inflation: Moderate pick-up of inflation expected - Interest Rates: Interest rates expected to rise - Currencies: Currencies appear balanced - Special Topic: Public deficits
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies; Public deficits